2017
DOI: 10.23954/osj.v2i4.1089
|View full text |Cite
|
Sign up to set email alerts
|

Type of Music on the Growth and Laying Performance, Behavior and Marketability of Quails

Abstract: A study was conducted to determine how different type of music influences the performance, egg quality, behavior and economics of raising Japanese quails. A total of 165 sexed day-old chicks was randomly assigned to five treatments and replicated three times with eleven quails (10 females and 1 male) per replication and was conducted from August to November, 2016. All data were subjected to ANOVA following the CRD and differences between treatments were subjected to Tukey's Test. Analysis revealed that quails … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 5 publications
1
5
1
Order By: Relevance
“…These results may be attributed to the favorable effect of enrichment on the physical and physiological condition that improves feeding habits and feed intake. In agreement with the current study, quails which provided with classical music showed higher final body weight than quails that were not provided with music (Cabaral et al, 2017). Also, layers that were provided with classical had higher feed intake and body weight (Davila et al, 2011).…”
Section: Hematological and Hormonal Analysissupporting
confidence: 92%
See 3 more Smart Citations
“…These results may be attributed to the favorable effect of enrichment on the physical and physiological condition that improves feeding habits and feed intake. In agreement with the current study, quails which provided with classical music showed higher final body weight than quails that were not provided with music (Cabaral et al, 2017). Also, layers that were provided with classical had higher feed intake and body weight (Davila et al, 2011).…”
Section: Hematological and Hormonal Analysissupporting
confidence: 92%
“…The first group was control had no environmental enrichment, while the second group was subjected to visual enrichment by using mirrors of 40cm length × 1.25m width fixed into the pen in the wall behind birds 40 cm from the wood shaving layer. The birds in the third group were subjected to auditory enrichment through using of classical music, which comes from a speaker hung 2 m height at one corner of the room, for 8 hours daily from 9.00 am to 5.00 pm; the volume of the music was measured using a sound meter (UNI-T Mini Sound Meter, China) and fixed at the normal sound volume up to 60 decibels (Cabaral et al, 2017).…”
Section: Experimental Designmentioning
confidence: 99%
See 2 more Smart Citations
“…There were mixed results regarding feeding behaviour and music availability. A study on other animals found that quails subjected to random, metallic, reggae, or classical music consumed significantly less food than quails not exposed to any form of music (Cabaral et al, 2017). Some other studies have shown results that contradict this study, whereby music was found not to influence the feeding behaviour of piglets, while classical music was observed to enhance broilers' feed intake and time spent eating (Li et al, 2019;Zhao et al, 2020).…”
Section: Discussioncontrasting
confidence: 72%